Reverse engineering through 3D optical scanning: Cylinder head (4G13) & side mirror case study / Aizah Adrianee Mardzuki - Mardzuki, Aizah Adrianee (2005)
Reverse Engineering is the process of reconstructing a computerized model from a digitized 3D object. Laser scanners are commonly used since they can sample 3D range images fast and very accurately relative to other technologies. In our approach, we will consider two method of reverse engineering. First, it will draw an existing parts using conventional method. Secondly, choose a part to redrawing using Rapid Form. Conventional method that used is measuring engine parts using manual equipment such as vernier caliper, ruler and micrometer. For these methods, engine components which will draw are cylinder head and all its components and also side mirror. This increases the complexity of in design and it is quite tedious since it will take much times and energy to reproduce it. Rapid Form is one of newest software in reverse engineering. By using it, component will scan to get the feature before it will modify till get the proper component. Comparison will be made to utilize these methods. This paper aimed to exhibit a computer aided reverse engineering approach in modeling a product through those methods. A comprehensive methodology is presented, and case study illustrated the approach.